Factors affecting the anthropometric and physical characteristics of elite academy rugby league players: A multiclub study - Dobbin, N.; Highton, J.; Moss, S. l.; Twist, C. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To investigate the factors affecting the anthropometric and physical characteristics of elite academy rugby league players. Methods: One hundred ninety-seven elite academy rugby league players (age = 17.3 [1.0] y) from 5 Super League clubs completed measures of anthropometric and physical characteristics during a competitive season. The interaction between and influence of contextual factors on characteristics was assessed using linear mixed modeling. Results: All physical characteristics improved during preseason and continued to improve until midseason, whereafter 10-m sprint ( 2 = .20 cf .25), countermovement jump (CMJ) ( 2 = .28 cf .30), and prone Yo-Yo Intermittent Recovery (Yo-Yo IR) test ( 2 = .22 cf .54) performance declined. Second ( 2 = .17) and third ( 2 = .16) -year players were heavier than first-years, whereas third-years had slower 10-m sprint times ( 2 = .22). Large positional variability was observed for body mass, 20-m sprint time, medicine-ball throw, CMJ, and prone Yo-Yo IR1. Compared with bottom-ranked teams, top-ranked teams demonstrated superior 20-m ( 2=-.22) and prone Yo-Yo IR1 ( 2 = .26) performance, whereas middle-ranked teams reported higher CMJ height ( 2 = .26) and prone Yo-Yo IR1 distance ( 2 = .20) but slower 20-m sprint times ( 2 = .20). Conclusion: These findings offer practitioners who design training programs for academy rugby league players insight into the relationships between anthropometric and physical characteristics and how they are influenced by playing year, league ranking, position, and season phase.